A novel carbonized derivative of Fe-Cu bimetallic organic framework (Fe-Cu-MOF@C): preparation and optimization. (3rd November 2022) - Guo, Shengxuan; Ren, Dajun; Huang, Yongwei; Wang, Zhaobo; Zhang, Shuqin; Zhang, Xiaoqing; Gong, Xiangyi
Abstract: A carbon derivative with Fe-Cu bimetallic organic framework (Fe-Cu-MOF@C) was prepared by microwave synthesis and pyrolysis. Using potassium persulfate (PS) as oxidant and 2, 4-dichlorophenol (2, 4-DCP) as target pollutant, the optimal preparation conditions of Fe-Cu-MOF@C were studied. The factors affecting the synthesis of Fe-Cu-MOF include microwave power, microwave time, microwave temperature, the molar ratio of metal ions to organic ligands, the molar ratio of iron and copper, etc. In addition, the influence of pyrolysis temperature on the performance of Fe-Cu-MOF@C cannot be ignored. The results show that Fe-Cu-MOF@C has the best catalytic performance when the microwave time is 30 min, the microwave power is 600 W, the microwave temperature is 150 °C, the molar ratio of (Fe 2+ + Cu 2+ )/H2 BDC is 10:3, the molar ratio of Fe 2+ /Cu 2+ is 10:1, and the pyrolysis temperature is 700 °C. After 90 min of reaction, 2, 4-DCP was completely removed. Repeatable experiments show that Fe-Cu-MOF@C has good stability and its service life can be restored by heat treatment. In this study, a heterogeneous catalyst with strong catalytic capacity, high stability and easy recovery was prepared by a simple and efficient process, which is conducive to the development of advanced oxidation technology and the progress of water environmental protection. HIGHLIGHTS: A new method for preparing carbonized derivatives of Fe-Cu bimetallic organic framework (Fe-Cu-MOF@C) based on microwave and pyrolysis was proposed. This material is an excellent catalyst for PS, which can efficiently and thoroughly degrade chlorophenol compounds in water. The optimum preparation conditions were determined. The material has good stability and long service life. Graphical Abstract